The Effect of a Multi-Layer HVOF Coating System (NiCr/CrC-NiCr + WC-Co 60:40) on Corrosion Resistance and Fatigue Behavior of Ti-6Al-4V Alloy - Fazly Arif; Riri Murniati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Ti-6Al-4V alloys are widely used in the aerospace and medical industries due to their superior strength-to-weight ratio, yet they remain susceptible to fatigue failure and corrosion in aggressive environments. This study aims to evaluate the effectiveness of multi-layer coating systems (NiCr/CrC-NiCr/WC-Co) deposited via the High Velocity Oxygen Fuel (HVOF) method in enhancing substrate surface integrity. A Systematic Literature Review (SLR) was conducted on 20 reputable international journals to synthesize data on microstructure, mechanical properties, and electrochemical performance. The results indicate that the HVOF technique produces highly dense coatings with porosity < 2%. The integration of a multi-layer system can increase surface hardness to above 900 HV and extend fatigue life by 15-25%. This improvement is driven by the induction of compressive residual stress and the crack deflection mechanism at the layer interfaces. Furthermore, the formation of a Cr_2 o_3 passive layer significantly reduces the corrosion rate in chloride media. This study concludes that graded coating design is an effective solution for the long-term protection of Ti-6Al-4V components operating under cyclic loads and corrosive environments.